Application Research of Traditional Chinese Motifs in Cultural and Creative Products - Qi, Zhao; Faridah, Sahari (Scientific Research Publishing, 2024)
As the treasures of Chinese history and culture, Traditional Chinese motifs have attracted extensive attention around the world. Over thousands of years of development, these time-honoured traditional motifs have been used in many areas of modern design, especially in Cultural and Creative product designs. These products are endowed with rich connotations and cultural features by designers and inherit Chinese traditional culture in their own unique way. Based on this, this paper focuses on the overview of traditional Chinese motifs, artistic characteristics and the significance of integration of traditional motifs with Cultural and Creative products, and explores the application of Traditional Chinese motifs in Cultural and Creative products.